A plausible involvement of GABAA/benzodiazepine receptor in the anxiolytic-like effect of ethyl acetate fraction and quercetin isolated from Ricinus communis Linn. leaves in mice - Vaishali Murade; Amit Waghmare; Deepali Pakhare; Sonali Dichayal; Rajesh Patil; Manish Wanjari; Shailendra Gurav; Dinesh Hase (Elsevier, 2021)
Ricinus communis Linn. (Euphorbiaceae) leaves are used in Indian traditional medicine to treat inflammatory and central nervous disorders. The polyphenolic compounds like quercetin (QUR), gallic acid, and rutin display an anxiolytic-like activity. These constituents are also present in Ricinus communis leaves; however there are no scientific investigations conducted to verify the anxiolytic-like effects of ethyl acetate fraction of Ricinus communis (RCLEA) leaves. HPLC technique was used to quantify the polyphenols contained in RCLEA fraction. It revealed the contents (% w/w): gallic acid (0.63), rutin (4.36), QUR (1.62) and Pyrogallol (PYR) (14.07). The present study investigated the anxiolytic-like effects of RCLEA fraction and two major polyphenols in Ricinus communis in experimental models of anxiety compared with a positive control diazepam (DZP) (1 mg/kg, i.p.). In order to investigate the anxiolytic-like effect, doses of RCLEA fraction (25, 50 and 100 mg/kg, i.p), QUR and PYR (1, 5 and 10 mg/kg respectively, i.p.) were administered to mice and subjected to open field test (OFT), elevated plus maze (EPM) or rota-rod test. The results of OFT revealed the significant increase in time spent in central area with treatments of RCLEA fraction (50 and 100 mg/kg, p < 0.05 and p < 0.01 respectively), QUR (10 mg/kg, p < 0.05) and PYR (10 mg/kg, p < 0.05). The reduction in rearings was observed with doses of RCLEA fraction, QUR and PYR. Significant reductions were found in defecation after treatments of RCLEA fraction and QUR and comparable to DZP. The results of OFT were further validated using EPM, showed that RCLEA fraction and QUR treatments (50 and 10 mg/kg, respectively) produced a significant increase in the time spent and entry into the open arms of elevated plus maze, with a profile comparable to that of DZP. No significant changes were observed in the rota-rod test, suggesting that the RCLEA fraction, QUR and PYR did not cause neurotoxicity, sedation and muscle relaxation commonly related to benzodiazepines. RCLEA fraction and QUR presented anxiolytic-like effect on the EPM, which was partially reversed by flumazenil suggested involvement of GABAA/benzodiazepine receptor. These results suggest that RCLEA fraction and QUR exerts anxiolytic-like effects, and its mechanism of action appears to be modulated by GABAA/benzodiazepine receptor also supported by molecular docking study.